Estonia en el mundo de entreguerras. Los países de la nueva Europa y la Sociedad de Naciones: el caso de los países Bálticos (Revista de Estudios Europeos, 2024)
The end of the Great War at the beginning of the 20th century brought about a change of political paradigm in Central and Eastern Europe. The change was especially relevant for Estonia, a small territory under foreign rule since the Middle Ages. The country's independence from the extinct Russian Empire and from German socioeconomic domination needed international support, a task that was adequately carried out by the recently established League of Nations. This research focuses on the influence of the international community on the formation of Estonia, its support, its political and economic solidarity, and its meaning in terms of protection against the existential threat posed by the Soviet Union.
Keywords: Estonia; League of Nations; International Cooperation; Baltic independence; International legality